(3CbGhjd GdChGFd aj WHGFY GdCZPjI hbhGgGs - (3ESMGb Hf SdjeGf GdGSQGFjdj, CHh jYbhH,J (B320 (3g` s
(3ChdgG (B:s
(3Efj LeYJ aj gPG GdcJGH LejY eG jMJGL Edi eYQaJg ef GdCZPjI eeG bGd LGdjfhS hZjQg aj CQHY ebGdGJ s
(3BNQgG (B:s
(3eHJhQ, jfJgj CKfGA GdebGdI GdQGHYI Hbhdg(B: (3hCeG ef cGf eQWhHkG aGdCaVd dbWY NeGQg TQH GdCaSfJjf hONhd GdMeGe hGdJYQa ajg Edi Cf jfMd GdNeGQ hJfTW GdWHGY ddZPGA TghJg s
(3GfXQ CjkVG Qbe (B23s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfj (B- (3U (B28 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs